Surgical and non-surgical treatment of periodontal diseases - Theodoro, Leticia Helena [UNESP]; Garcia, Valdir Gouveia [UNESP] (Wiley, 2015)
High power lasers have been used in periodontics mainly for the surgical treatment of soft tissues and in non-surgical periodontal treatments such as therapy for sulcular or periodontal pocket debridement, reduction of subgingival bacteria, and scaling and root planing (SRP). CO2, Nd:YAG and Nd:YAP, and semiconductor diode lasers were the first to be recommended for treating soft tissues in the field of periodontics; Nd:YAG and semiconductor diode lasers have also been used to reduce microbes in periodontal pockets. Periodontal laser surgery is also indicated for cases of enlarged clinical crowns or to remove excess gingival tissue caused by trauma, bacterial plaque, medications, or passive eruption. The use of high power lasers during periodontal surgery has proven advantageous in the improvement of tissue repair, because these devices facilitate a more conservative technique without discomfort during or after the surgery and without postoperative sensitivity, pain, or bleeding.
Keywords: High power lasers; Nd:YAG laser; Non-surgical treatment; Periodontal laser surgery; Periodontal pockets; Postoperative sensitivity; Scaling and root planing (SRP); Semiconductor diode lasers; Soft tissues; Surgical treatment